The Armory Show 2007 : International fair of new art - New York. (New York : The Armory Show New York, 2007)
Abdessemed, Adel ; Aitken, Doug ; Akakce, Haluk ; Allen, Tom ; Amm, Markus ; Appel, Kevin ; Attia, Kader ; Auer, Auer ; Banner, Fiona ; van Bart, Hannah ; Ben-Gal, Avner ; Benassi, Elisabetta ; Beshty, Walead ; Bessone, Amy ; Boyan ; Boyce, Martin ; Bradley, Slater ; Büchel, Christoph ; Byrne, Nick ; Carron, Valentin ; Cecchini, Loris ; Chan, Paul ; Chun, Kwang-Young ; Cline, Michael ; Cordova, William ; Cottingham, Keith ; Crow, Rosson ; Crumb, Robert ; Damasceno, José ; Deroubaix, Damien ; Doig, Peter ; Dole-Recio, Lecia ; Van Dongen, Iris ; Ebner, Shannon ; Emin, Tracey ; Eneblom, Niklas ; Enomoto, Koichi ; Fisher, Naomi ; Flannigan, Moyna ; Frank, Natalie ; Gabbiani, Francesca ; Gabellone, Giuseppe ; Gander, Ryan ; Geis, Axel ; Gelatin ; Gelitin ; Gilmore, Kate ; Gmelin, Felix ; Gordon, Daniel ; Gormley, Antony ; Graf, Franz ; Grannan, Katy ; Greenfort, Tue ; Gupta, Subodh ; Haendel, Karl ; Finlay, Ian Hamilton ; Hammond, Charlie ; Hardy, Anne ; Herold, Jörg ; Hilding, Tommy ; Hiorns, Roger ; Hirschhorn, Thomas ; Hoeber, Julian ; Hofer, Andreas ; Höfer, Candida ; Holstad, Christian ; Houshiary, Shirazeh ; Hume, Gary ; Hyungkoo Lee ; Ikeda, Mitsuhiro ; Jansson, Kristina ; Jezik, Enrique ; Johnson, Butt ; de Jong, Folkert ; Jung, Yeondoo ; Kass, Deborah ; Kay, Edward ; Kelley, Mike ; Kentridge, William ; Kimsooja ; Kleckner, John ; Koh, Terence ; Kolkoz ; Koumoundouros, olga ; Krebber, Michael ; Kruip, Germaine ; Kusama Yayoi ; Lambie, Jim ; Landy, Michael ; Van Lankveld, Rezi ; Lansing-Dreiden ; Lawler, Louise ; van Lieshout, Erik ; Lozek, Jörg ; MacKinven, Alastair ; Maluka, Mustafa ; Man, Victor ; Mancuska, Jano ; Mannig, Martin ; Marker, Chris ; Marshall, Kerry James ; Mayaux, Philippe ; McCaslin, Matthew ; McCollum, Allan ; McGinness, Ryan ; etc.
The Armory Show 2007 : International fair of new art. Pier, New York, 2007-02-23. 2007-02-26
boek